Post-imperialism, postcolonialism and beyond: towards a periodisation of cultural discourse about colonial legacies - Göttsche, Dirk (SAGE, 2017)
Taking German history and culture as a starting point, this essay suggests a historical approach to reconceptualising different forms of literary engagement with colonial discourse, colonial legacies and (post-) colonial memory in the context of Comparative Postcolonial Studies. The deliberate blending of a historical, a conceptual and a political understanding of the ‘postcolonial’ in postcolonial scholarship raises problems of periodisation and historical terminology when, for example, anti-colonial discourse from the colonial period or colonialist discourse in Weimar Germany are labelled ‘postcolonial’. The colonial revisionism of Germany’s interwar period is more usefully classed as post-imperial, as are particular strands of retrospective engagement with colonial history and legacy in British, French and other European literatures and cultures after 1945. At the same time, some recent developments in Francophone, Anglophone and German literature, e.g. Afropolitan writing, move beyond defining features of postcolonial discourse and raise the question of the post-postcolonial.